2013
DOI: 10.2147/oajsm.s39632
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quercetin supplementation reduces lipid peroxidation but does not improve performance in endurance runners

Abstract: PurposeTo evaluate the effects of chronic quercetin supplementation on endurance performance and antioxidant status in long distance runners. We hypothesized that an improved antioxidant status can be associated with enhanced performance.MethodsDuring 6 weeks of supplementation utilizing a double blind, randomized design, young male subjects received quercetin (1000 mg/day) or placebo while maintaining their current training schedules.ResultsFollowing the end of the supplementation period, there was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…However, PO max increased 19% in the post-supplementation period compared to baseline values, although this was not statistically significant.These findings are consistent with published values on the ergogenic effect of quercetin supplementation in humans [16][17][18][19], although contrary findings have also been reported [20,38,39]. Furthermore, Scholten&Sergeev have found that quercetin supplementation (6 week, 1000 mg/day) did not enhance performance as measured by VO2 peak running economy, heart rate, and rating of perceived exertion but quercetin can reduced oxidative stress as measured by malondialdehyde as a marker of lipid peroxidation [40]. Ganio et al found that 5 days of quercetin supplementation did not improve VO2max in untrained, sedantary individuals [38].…”
Section: Discussionsupporting
confidence: 90%
“…However, PO max increased 19% in the post-supplementation period compared to baseline values, although this was not statistically significant.These findings are consistent with published values on the ergogenic effect of quercetin supplementation in humans [16][17][18][19], although contrary findings have also been reported [20,38,39]. Furthermore, Scholten&Sergeev have found that quercetin supplementation (6 week, 1000 mg/day) did not enhance performance as measured by VO2 peak running economy, heart rate, and rating of perceived exertion but quercetin can reduced oxidative stress as measured by malondialdehyde as a marker of lipid peroxidation [40]. Ganio et al found that 5 days of quercetin supplementation did not improve VO2max in untrained, sedantary individuals [38].…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that supplementation of trained participants with 1,000 mg/d of quercetin for 6 weeks tends to increase VO 2 max , suggesting a slight improvement in cardiorespiratory fitness through reducing oxidative stress. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 12 14 However, it remains unclear whether quercetin supplementation increases antioxidant status or reduces oxidative stress, leading to enhanced physical performance. 4 , 15 18 …”
Section: Introductionmentioning
confidence: 99%
“…We did not identify any adaptations in response to quercetin treatment that would exert an ergogenic effect on endurance performance. While many studies have reported quercetin's ergogenic effect on endurance exercise [6][7][8][9], other studies have shown no effect of chronic quercetin treatment [11,36,37]. Importantly, Casuso et al [27] demonstrated that chronic quercetin treatment and exercise training impaired training-induced citrate synthase adaptation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%